2019
DOI: 10.1073/pnas.1903982116
|View full text |Cite
|
Sign up to set email alerts
|

Pulcherrimin formation controls growth arrest of the Bacillus subtilis biofilm

Abstract: Biofilm formation by Bacillus subtilis is a communal process that culminates in the formation of architecturally complex multicellular communities. Here we reveal that the transition of the biofilm into a nonexpanding phase constitutes a distinct step in the process of biofilm development. Using genetic analysis we show that B. subtilis strains lacking the ability to synthesize pulcherriminic acid form biofilms that sustain the expansion phase, thereby linking pulcherriminic acid to growth arrest. However, pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(80 citation statements)
references
References 63 publications
12
68
0
Order By: Relevance
“…We also see PchR activation in late-stage biofilm, glucose exhaustion, and phosphate starvation experiments. These results agree with a recent study that found pulcherrimin to be an important intercellular signal for the stationary phase that also helps exclude competing bacteria from established biofilms 47 . The regulation mechanisms of iModulons like this one can be the subject of future research.…”
Section: Resultssupporting
confidence: 93%
“…We also see PchR activation in late-stage biofilm, glucose exhaustion, and phosphate starvation experiments. These results agree with a recent study that found pulcherrimin to be an important intercellular signal for the stationary phase that also helps exclude competing bacteria from established biofilms 47 . The regulation mechanisms of iModulons like this one can be the subject of future research.…”
Section: Resultssupporting
confidence: 93%
“…We also see PchR activation in late stage biofilm, glucose exhaustion, and phosphate starvation experiments. These results agree with a recent study that found pulcherrimin to be an important intercellular signal for the stationary phase that also helps exclude competing bacteria from established biofilms 38 . The regulation mechanisms of i-modulons like this one can be the subject of future research.…”
Section: I-modulons Generate Novel Hypotheses I-modulon Activities Csupporting
confidence: 93%
“…For instance, we observed that the iron chelator pulcherrimin was active in stationary phase signaling in B. subtilis ( 23 ). This observation was recently externally validated ( 24 ). More broadly, each decomposition explained 65–80% of the variance in the transcriptomic data sets, indicating that the functions and regulators identified captured most of the transcriptional functions of the TRNs under the conditions where the data was obtained.…”
Section: Introductionmentioning
confidence: 58%